Motivating cultural heritage artifacts presentation using persuasive technology - Vičič, Jernej; Šukljan, Tine (Informatica, 2016)
We have developed an information system in the scope of a project for the preservation and popularization of architectural heritage. The system aims at promoting archaeological tourism and contains a mobile application and an interactive on-line application. The mobile application guides the user on a pre-prepared learning paths and draw attention to the points of interest in the vicinity. At each point of interest it proposes to the user a choice of the level of information, he wants to learn. The user is motivated using persuasive technologies. The backbone of the system is a web server which serves as a main entry point for adding paths into the system and as a feeder of the data for both the mobile and online application.